2016
DOI: 10.1097/bpo.0000000000000475
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Mass Index on Postoperative Morbidity After Orthopaedic Surgery in Children With Cerebral Palsy

Abstract: Level III-Prognostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
0
21
0
2
Order By: Relevance
“…NSQIP-P has been used to describe adverse events following common pediatric orthopedic procedures in order to identify procedures and patient characteristics associated with an increased risk of postoperative complications [26]. Other studies have considered outcomes after specific orthopedic procedures [27][28][29], most frequently involving the spine [30][31][32][33], as well as outcomes in orthopedic patients with specific risk factors such as obesity, congenital heart disease, or cerebral palsy [34][35][36]. To our knowledge, NSQIP-P has not been used to characterize outcomes after pediatric orthopedic oncology procedures.…”
Section: Introductionmentioning
confidence: 99%
“…NSQIP-P has been used to describe adverse events following common pediatric orthopedic procedures in order to identify procedures and patient characteristics associated with an increased risk of postoperative complications [26]. Other studies have considered outcomes after specific orthopedic procedures [27][28][29], most frequently involving the spine [30][31][32][33], as well as outcomes in orthopedic patients with specific risk factors such as obesity, congenital heart disease, or cerebral palsy [34][35][36]. To our knowledge, NSQIP-P has not been used to characterize outcomes after pediatric orthopedic oncology procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kato et al investigated cervical spine in patients with athetoid CP who underwent posterior decompression surgery ( n = 31) and multivariate analysis showed that pedicle sclerosis associated with a higher risk of breach of cervical pedicle screws ( 71 ). Further, Minhas et al evaluated the effect of body mass index class on complications after orthopedic surgery in children with CP ( n = 1,746) and multivariate logistic regression analysis revealed that underweight status was the risk factor for complications in osteotomies and spine surgery ( 76 ). The risk factors identified by these studies are helpful to avoid the surgical complications and improve surgical treatments in CP.…”
Section: Multivariate Analysis In Cp Outcome Evaluationmentioning
confidence: 99%
“…Taken together, since there is no cure for CP yet, and the death rate of CP is high (~8%), there is much to do to improve the outcomes of CP, and multivariate analytic approaches may play a bigger role in meeting such clinical demands. Surgical outcome predictors and risk factors for complications in CP surgical treatments have been identified by a number of multivariate outcome studies ( 63 , 64 , 67 , 69 , 71 , 73 , 76 ), which are useful not only for outcome evaluation and prediction but also for avoiding complications and improving surgical treatments in CP. However, there are few outcome studies for medications and supportive treatments (such as physical therapy) in CP using multivariate analysis.…”
Section: Multivariate Analysis In Cp Outcome Evaluationmentioning
confidence: 99%
“…This population often has such a high level of spasticity that the tone is essentially burning all the calories they can ingest, so the patient very often is undernourished, which is known to increase risk. 4 Lam et al did acknowledge that BMI for all patients, surgical technique, and preoperative preparation could not be considered for this study as they were not available in the NSQIP-P database. As these and other data points are known to contribute to complication risk, expanding the database to include these variables may assist in improving protocols for preoperative preparation.…”
mentioning
confidence: 99%
“…In addition, the BFMF describes functional capacity and may under-report difficulties in manual skills in the unilateral or less severe presentations seen in this cohort. This is compared to an alternative measure, the Manual Ability Classification System, 4 which also incorporates environmental and personal factors affecting manual ability as defined in the ICF. 3 The Stroke in Childhood guideline includes recommendations for broad multidisciplinary assessment at regular intervals to guide rehabilitation provision and monitor progress and outcome.…”
mentioning
confidence: 99%